Circular dorsal ruffles : a mode of steering cells - Kamaladasan Kalidasan (2019)
Circular Dorsal Ruffles (CDRs) are actin rich, ring-shaped structures that form across the dorsal surface of certain cell types upon stimulation by growth factors. Although previous studies have implicated the formation of CDRs as a Rac1 dependent process, substrate stiffness experiments have hinted a role for RhoA and its effectors. Herein, how RhoA and its effectors could affect CDR formation and its dynamics were investigated. It was found that RhoA and Rac1 have clear distinct zones of activation in CDRs. As a result, their effectors namely, mDia1 and Arp2/3 can co-operate to produce actin filaments to support the CDR structure. Interestingly, actomyosin contractility was found to be responsible for sustaining CDRs and that POPX2 phosphatase could harness enhanced localised actomyosin contractility to promote CDR formation. In addition, focal adhesions serve as anchors to accommodate CDRs when they traverse on the dorsal surface. In this study, I also found that CDRs can act as actin reservoirs from which actin can be re-directed to the leading edges after CDR disassembly. Surprisingly, the actomyosin network is also observed to move towards the leading edge after CDR disassembly. Consequently, cells that exhibit CDRs display enhanced directional migration persistence. This opens avenues to study CDRs in myriad cell migration contexts to better understand their biological function.